2014
DOI: 10.1177/0961203314563818
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of disease activity and response to treatment in a large Spanish cohort of patients with systemic lupus erythematosus

Abstract: A significant percentage of patients have moderately-to-severely active SLE at some stage. Disease activity has a big impact in terms of need for treatment and cause of hospitalization. The effectiveness of the standard therapies for reducing disease activity is clearly insufficient. Some clinical features are associated with refractory SLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 45 publications
0
17
0
5
Order By: Relevance
“…In a separate assessment, thrombocytopenia was also assumed for a platelet count of <150000/mm 3 . Results of ferritin and direct Coombs' tests are saved for anemic patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a separate assessment, thrombocytopenia was also assumed for a platelet count of <150000/mm 3 . Results of ferritin and direct Coombs' tests are saved for anemic patients.…”
mentioning
confidence: 99%
“…Hematological involvement was classified such that a hemoglobin count of <13gr/dL in males and <12gr/dL in females was considered as anemia, and likewise, a leukocyte count of <4000/mm 3 as leukopenia, an absolute lymphocyte count of <1500/mm 3 as lymphopenia, an absolute neutrophil count of <1500/mm 3 as neutropenia, and a platelet count of <100000/ mm 3 as thrombocytopenia. In a separate assessment, thrombocytopenia was also assumed for a platelet count of <150000/mm 3 .…”
mentioning
confidence: 99%
“…N = 5/group. of treatment for lupus (Pego-Reigosa et al, 2015). This study demonstrated that the short-term changes of gut microbiota before onset affected not only therapeutic efficiency of prednisone but also the targeted gut microbiota of prednisone.…”
Section: Discussionmentioning
confidence: 66%
“…Анализ публикаций последних лет позволяет с уверенностью говорить о достаточно серьез-ных проблемах, стоящих перед современной ревматологи-ей. Так, в работах испанских и немецких исследователей подчеркивается, что, несмотря на проводимую терапию, активность СКВ остается высокой, а у 25% больных на-блюдается рефрактерное течение заболевания [5,23].…”
Section: данные когортных исследований и регистров за рубежомunclassified
“…В последние годы значительно возрос интерес к изучению больших когорт и регист-ров больных СКВ. Такие исследования позво-ляют выявить взаимосвязь пола, возраста, эт-нической принадлежности с особенностями дебюта и дальнейшего течения СКВ, охарак-теризовать субтипы болезни, причины разви-тия органных НП, эффективность и безопас-ность различных терапевтических программ, определить роль и место новых инновацион-ных методов лечения, оптимизировать мето-ды ранней диагностики и прогнозирования исходов СКВ [23,34,47,48].…”
unclassified